Targeting FLT3 to treat leukemia - Helmut König; Mark J. Levis (2014)
Introduction: Approximately 23% of acute myeloid leukemia (AML) patients younger than 60 years of age carry a mutation in the transmembrane domain of the FMS-like tyrosine kinase-3 (FLT3) gene (FLT3/internal tandem duplications [ITD]). In normal karyotype AML, the presence of a FLT3/ITD mutation is associated with poor prognosis, as mirrored by a high risk of relapse even after allogeneic stem cell transplantation. The poor prognostic impact along with the observation that FLT3 is frequently overexpressed in the majority of AML cases has formed the platform for the development of FLT3-targeted strategies. To date, several FLT3 kinase inhibitors have been investigated in preclinical and clinical studies. However, as of yet, none of the studied FLT3 inhibitors has received FDA approval for routine clinical use in AML. This is in part due to the 'off target' effects observed with most inhibitors when administered at concentrations needed to achieve sustained levels of FLT3 inhibition, which are required to exhibit substantial cytotoxic effects against leukemic blasts. Furthermore, the development of resistance mutations has emerged as a clinical issue posing a threat to successful FLT3 inhibitor therapy.Areas covered: In this review, the authors provide a brief summary of FLT3 inhibitors investigated thus far, and discuss current treatment approaches and strategies how to best incorporate FLT3 tyrosine kinase inhibitors (TKIs) into therapy.Expert opinion: The combination of a FLT3 inhibitor with conventional chemotherapeutic regimens, epigenetic modifiers or inhibitors of FLT3 downstream and collateral effectors has emerged as a promising strategy to improve treatment outcome. The future of a tailored, molecular-based treatment approach for FLT3-mutated AML demands novel clinical trial concepts based on harmonized and aligned research goals between clinical and research centers and industry.